Proyecto arquitectónico central de abastos para la localidad de Suba (2021)
In this project, an investigation was carried out based mainly on the food that is wasted in the world annually, the country of Colombia and specifically in the city of Bogotá. A strategy was focused and developed, through which an improvement in the food supply system present in Bogotá is proposed, through the complement of four wholesale food distribution centers, two of them existing, one proposed by Marín & Reyes, 2015 and finally a central food supply located in the town of Suba, where through the various analyzes presented in this research, it was determined that this sector has various characteristics that make the project adequate. In this way, the system is concentrated in strategic points in the city, allowing food transfer times to be reduced and therefore the percentage of food loss generated in the distribution and retail process to decrease. In addition, the project contemplates eco-friendly systems and design strategies that improve the social conditions of the intervened sector.